2009
DOI: 10.1097/mnm.0b013e32832eabec
|View full text |Cite
|
Sign up to set email alerts
|

Small field-of-view cardiac SPECT can be implemented on hybrid SPECT/CT platforms where data acquisition and reconstruction are guided by CT

Abstract: Projection truncation due to small FOV cameras in cardiac SPECT/CT can lead to significant errors. TMOSEM guided by nontruncated CT reconstruction shows promise in reducing these errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…As previously described by Xiao et al small field of view SPECT may exclude the liver from the field of view and thus interfere with scatter correction. 2,3 In our patient, the liver was not excluded and, however, truncation of the distal one-third of the heart was observed. Although the truncation artifact in our case was eventually recognized by the interpreting physician after the scan was completed and the patient had already left the facility, it had not been recognized by the imaging technologist.…”
mentioning
confidence: 56%
“…As previously described by Xiao et al small field of view SPECT may exclude the liver from the field of view and thus interfere with scatter correction. 2,3 In our patient, the liver was not excluded and, however, truncation of the distal one-third of the heart was observed. Although the truncation artifact in our case was eventually recognized by the interpreting physician after the scan was completed and the patient had already left the facility, it had not been recognized by the imaging technologist.…”
mentioning
confidence: 56%
“…18 Third, for iterative methods, the system matrix (SM) must be large enough to contain the entire object even if only a ROI is to be reconstructed. In addition, with the fulfillment of these conditions, studies also demonstrated that the use of body contour as a support in reconstruction could effectively reduce bias and artifacts caused by projection truncation in both transmission 9,19 and emission 12,15,20 applications. A more recent study suggested that when projections are truncated, sufficient angular sampling (e.g., >60 views over 180 • rotation) is required to have a quantitative and artifact free reconstruction, otherwise the solution is not unique even when a subregion value is known as a priori knowledge.…”
Section: Introductionmentioning
confidence: 97%
“…13,14 Sabodjian et al simulated a small FOV system (16 × 16 cm) by artificially truncating the data from patient studies acquired on a two-head GE Infinia-Hawkeye system, and showed that the reconstructions of the truncated projections yielded over 100% overestimation in the myocardium, and on average a 17% reduction in defect size. 15 Xiao et al, on the other hand, investigated the impact of truncations that occurred only in the axial direction. Their results suggested that the impact of truncations on single isotope SPECT was insignificant and should not affect clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the principle of tomography, images cannot be reconstructed accurately using truncated projection data [3]. Therefore, an artifact, known as a truncation artifact occurs in reconstructed tomographic images [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of truncation artifacts in myocardial perfusion SPECT have reported on the effects of the attenuation maps generated from a truncated transmission data on the reconstructed image [4][5][6][7]. On the other hand, a few studies have investigated whether the truncation artifact affects the myocardial image without attenuation correction if the myocardial image is not truncated outside the FOV at any projection view, but the radioactivity of body tissue is truncated at some views [8][9][10]. Image reconstructed from truncated projection data display various artifacts and distortions.…”
Section: Introductionmentioning
confidence: 99%